2014
DOI: 10.1093/mnras/stu1378
|View full text |Cite
|
Sign up to set email alerts
|

Extensive HST ultraviolet spectra and multiwavelength observations of SN 2014J in M82 indicate reddening and circumstellar scattering by typical dust

Abstract: SN 2014J in M82 is the closest detected Type Ia supernova (SN Ia) in at least 28 years and perhaps in 410 years. Despite its small distance of 3.3 Mpc, SN 2014J is surprisingly faint, peaking at V = 10.6 mag, and assuming a typical SN Ia luminosity, we infer an observed visual extinction of A V = 2.0 ± 0.1 mag. But this picture, with R V = 1.6 ± 0.2, is too simple to account for all observations. We combine 10 epochs (spanning a month) of HST/STIS ultraviolet through near-infrared spectroscopy with HST/WFC3, K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
174
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(193 citation statements)
references
References 84 publications
17
174
2
Order By: Relevance
“…For SN 2014J we also add E(B − V) = 1.37 mag (R V = 1.4) for M82. We refer to Amanullah et al (2014), Foley et al (2014), Goobar et al (2014), and Johansson et al (2014) for a discussion of those values. For the recession velocities to the supernovae, we use the host galaxy recessions, i.e., +241 ± 2 km s −1 for SN 2011fe and +203 ± 4 km s −1 for SN 2014J (de Vaucouleurs et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For SN 2014J we also add E(B − V) = 1.37 mag (R V = 1.4) for M82. We refer to Amanullah et al (2014), Foley et al (2014), Goobar et al (2014), and Johansson et al (2014) for a discussion of those values. For the recession velocities to the supernovae, we use the host galaxy recessions, i.e., +241 ± 2 km s −1 for SN 2011fe and +203 ± 4 km s −1 for SN 2014J (de Vaucouleurs et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Their results, with reddening values of E(B − V) ∼ 1.3 and R V ∼ 1.4, are compatible with a power-law extinction, expected in the case of multiple scattering scenarios. In the same wavelength band, from UV to near infrared (NIR), Foley et al (2014) found reddening parameter values of E(B − V) ∼ 1.2 and R V ∼ 1.4. In this model, the extinction is explained to be caused by a combination of the galaxy dust and a dusty circumstellar medium.…”
Section: Introductionmentioning
confidence: 99%
“…This SN is highly reddened and thus offer the best opportunity to study the extinction property on its sightline. The extensive observations have revealed that the extinction curve derived for SN 2014J is highly steep with a very low value of R V ≃ 1.5 (e.g., Goobar et al, 2014;Amanullah et al, 2014;Foley et al, 2014;Marion et al, 2015). From a simultaneous fit to the extinction and polarization data, Hoang (2015) claim that both interstellar and circumstellar dust are responsible for the anomalous extinction property toward SN 2014J.…”
Section: Introductionmentioning
confidence: 99%